Assessment of Matrix Gla Protein, Klotho Gene Polymorphisms, and Oxidative Stress in Chronic Kidney Disease - (:unkn) unknown (INFORMA HEALTHCARE, 2011)
Increased vascular calcification and oxidative stress are considered as extra renal risk factors at the pathogenesis cardiovascular events in chronic kidney disease (CKD). We investigated matrix Gla protein (MGP) (T-138C, Glu60X, Thr83Ala) and Klotho (Cys370Ser) gene polymorphisms, serum MGP levels, and oxidative stress status of 84 CKD patients and 37 healthy controls. The MGP gene Glu60X and Thr83Ala polymorphisms were significantly associated with CKD. The correlation between T-138C genotype of MGP gene, Cys370Ser genotype of Klotho gene, and CKD was not significant (p > 0.05). At the haplotype analysis, the combination of the X allele of Glu60X and the Thr allele of Thr83Ala showed a significantly increased risk of CKD (p < 0.05). X allele, Thr allele, and C allele of T-138C were associated with diabetes mellitus and CKD phenotypes occurring concurrently (p < 0.01). Serum zinc levels were significantly low in end-stage renal disease (ESRD) patients (p = 0.0001). The total comet score frequency of ESRD patients was higher than that of control group (p < 0.05). The urinary 8-hydroxy-2'-deoxyguanosine levels were significantly high in CKD patients (p < 0.05). According to this study, analyzing the distribution of MGP gene and oxidative stress status would be very informative in order to detect their role at CKD.
Keywords: chronic kidney disease; end-stage renal disease; genetic polymorphism; matrix Gla protein gene; Klotho gene; oxidative DNA damage; STAGE RENAL-DISEASE; CARBOXYGLUTAMIC ACID PROTEIN; VASCULAR CALCIFICATION; CARDIOVASCULAR MORTALITY; HEMODIALYSIS-PATIENTS; POSTMENOPAUSAL WOMEN; FUNCTIONAL VARIANT; KEUTEL-SYNDROME; HORMONE KLOTHO; BONE-DENSITY